Novel o-naphthoquinones induce apoptosis of EL-4 T lymphoma cells through the increase of reactive oxygen species - Di Rosso, María Emilia (2013)
Novel β-lapachone analogs 2-phenyl-3,4-dihydro-2H-benzo[h]chromene-5,6-dione (NQ1), 2-p-tolyl-3,4-dihydro-2H-benzo[h]chromene-5,6-dione (NQ3) and 2-methyl-2-phenyl-3,4-dihydro-2H-benzo[h]chromene-5,6-dione (NQ7), which have trypanocidal activity, were assayed for cytotoxic effects on murine EL-4 T lymphoma cells. The NQs inhibited the proliferation of EL-4 cells at concentrations above 1 μM. Nuclear staining of the EL-4 cells revealed chromatin condensation and a nuclear morphology compatible with the induction of apoptosis. Flow cytometry assays with annexin V-FITC and propidium iodide confirmed the cell death by apoptosis. Using electron paramagnetic resonance (EPR), a semiquinone radical was detected in EL-4 cells treated with NQs. In addition, a decrease in the GSH level in parallel with reactive oxygen species (ROS) production was observed. Preincubation with n-acetyl-l-cysteine (NAC) was able to reverse the inhibitory effects of the NQs on cell proliferation, indicating that ROS generation is involved in NQ-induced apoptosis. In addition, the NQs induced a decrease in the mitochondrial membrane potential and increased the proteolytic activation of caspases 9 and 3 and the cleavage of Poly (ADP-Ribose) Polymerase (PARP). In conclusion, these results indicate that redox cycling is induced by the NQs in the EL-4 cell line, with the generation of ROS and other free radicals that could inhibit cellular proliferation as a result of the induction of the intrinsic apoptosis pathway.